2015 IEEE First International Conference on Big Data Computing Service and Applications 2015
DOI: 10.1109/bigdataservice.2015.62
|View full text |Cite
|
Sign up to set email alerts
|

Analytics: Key to Go from Generating Big Data to Deriving Business Value

Abstract: The potential to extract actionable insights from big data has gained increased attention of researchers in academia as well as several industrial sectors. The field has become interesting and problems look even more exciting to solve ever since organizations have been trying to tame large volumes of complex and fast arriving big data streams through newer computing paradigms. However, extracting meaningful and actionable information from big data is a challenging and daunting task. The ability to generate val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The potential to extract actionable insights from Big Data has gained increased attention of researchers in academia as well as several industrial sectors. The ability to generate value from large volumes of data is an art which combined with analytical skills needs to be mastered in order to gain competitive advantage in business (Arora & Malik, 2015).…”
Section: Annual Scientific Productionmentioning
confidence: 99%
“…The potential to extract actionable insights from Big Data has gained increased attention of researchers in academia as well as several industrial sectors. The ability to generate value from large volumes of data is an art which combined with analytical skills needs to be mastered in order to gain competitive advantage in business (Arora & Malik, 2015).…”
Section: Annual Scientific Productionmentioning
confidence: 99%
“…here we climb to the next level of the DIKW hierarchy. Thus, big data analytic capabilities have gained much attention recently (Akter and Fosso Wamba, 2016;Arora and Malik, 2015;Fosso Wamba et al, 2017). Analytical capabilities are human centric, such as building a predictive analytics model, or interpreting a business need into an algorithm.…”
Section: Capability Creation Processmentioning
confidence: 99%
“…In the work it is found that the interactivity and the quality of posts may be much more successful than the bare number of posts and of fans. Finally, the work in [5] suggests to fruitful employ social big data analytics to identify strategies for retaining customers before they decide to leave a company for a competitor. This fits perfectly the logic of the customer lifetime value, defined as the present value of all existing and future cash flows generated from a customer [95].…”
Section: Managing Customer Relationshipmentioning
confidence: 99%